M&E and Budget Program Performance Measurement in Ukraine: Current State and Needs for Improvement - Sergii Slukhai (European Financial and Accounting Journal, 2011)
The key elements of a performance-based budgeting methodology have already become a part of the mechanism for public expenditure management in Ukraine. At the same time, there still remains the issue of linking budget expenditures to specific results achieved by specific budget programs which defines the necessity of applying modern approaches to carrying out M&E. This study presents an analysis of the current state of M&E in Ukrainian public expenditure program management and offers some solutions which could improve its functioning. The analysis has revealed the absence of rigorous selection of performance indicators to evaluate budget program implementation, a need to better institutionalize the monitoring and evaluation activities through functional differentiation of budget programs and changes in approaches to their assessment.
Keywords: H50; 650; Performance-based budgeting; Monitoring; Evaluation; Budget program; Major spending unit